2017
DOI: 10.26873/svr-360-2017
|View full text |Cite
|
Sign up to set email alerts
|

SWINE BRUCELLOSIS CAUSED BY Brucella suis BIOVAR 2 IN CROATIA

Abstract: Brucellosis in swine was surveyed from 2011 to 2015 in 13 counties in Croatia. A total of 3230 breeding males were tested serologically, and positive reactions were confirmed in 42 (1.3%) males from 17 farms. A total of 641 sows with abortion or reproductive problems were tested, and positive reactions were confirmed in 34 (5.3%). Organs from 68 swine were tested for bacteria, and Brucella spp. was isolated from 47 (69.1%). B. suis was identified in 45 isolates from domestic swine and 2 isolates from wild boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Our study revealed the true seroprevalence of Brucella infection in the wild boar population of 9.06%, and shows the first published data regarding Brucella seropositivity in the wild boar population in Serbia, to date. The presence of Brucella in the wild boar population in Serbia was not unexpected since this microorganism has been confirmed in neighbouring countries, where B. suis biovar 2 was predominantly isolated [ 25 , 26 ]. Moreover, Cvetnic et al [ 14 ] confirmed the presence of B. suis biovar 3 in wild boars.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our study revealed the true seroprevalence of Brucella infection in the wild boar population of 9.06%, and shows the first published data regarding Brucella seropositivity in the wild boar population in Serbia, to date. The presence of Brucella in the wild boar population in Serbia was not unexpected since this microorganism has been confirmed in neighbouring countries, where B. suis biovar 2 was predominantly isolated [ 25 , 26 ]. Moreover, Cvetnic et al [ 14 ] confirmed the presence of B. suis biovar 3 in wild boars.…”
Section: Discussionmentioning
confidence: 97%
“…A global comprehensive literature review and meta-analysis of Brucella in pigs from 2000 to 2020 reported that the overall prevalence of brucellosis in wild boars between 2006 and 2010 was 22.3% [ 27 ], while after 2010, the prevalence gradually decreased after the World Organisation for Animal Health (WOAH) proposed control safety standards for animal production [ 28 ]. De facto , the Brucella seroprevalence in wild boars in Croatia varied through the years, ranging from 1.3% to 27.6% during different periods [ 13 , 14 , 25 ]. These data are in accordance with our obtained results, showing a Brucella seroprevalence of 9.06%.…”
Section: Discussionmentioning
confidence: 99%
“…is a genus currently consisting of 13 species (Ledwaba et al, 2019), in contrast to the 6 species known in 2003 (Osterman and Moryion, 2003). Brucellae are known to infect wild and domestic animals such as wild boars, cows, sheep, goats, dogs (Godfroid, 2002), but have also recently been cultured from marine animals, common voles, red foxes, baboons, human breast implants and fish (Al Dahouk et al, 2007;Cvetnic et al, 2017;Scholz et al, 2008aScholz et al, , 2008bScholz et al, , 2010Scholz et al, , 2016Whatmore et al, 2014). Brucella suis was the first pathogen to be used as a bioweapon in the 1950s.…”
Section: Introductionmentioning
confidence: 99%